2018
DOI: 10.15244/pjoes/76182
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of Radioactive and Heavy-Metal Contamination on Soil Enzyme Activity in a Former Uranium Mine

Abstract: Radioactivity and heavy metal toxicity of multi-metal deposits coexisting with the element uranium (U) could have long-term adverse impacts on soil biological processes and the health of soil ecosystems. Soil enzyme activities are considered bioindicators for assessing soil health. An experiment was designed to investigate invertase and ß-glucosidase activity in multi-metal deposits. Radioactivity and heavy metals were also investigated during this study. Our results showed that the invertase and ß-glucosidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…This result is contrary to the results of Gang et al (2017); Tang et al (2019) who revealed significant inhibition of soil enzymes by increases of heavy metals. Furthermore, high temperature and pH at contaminated locations encourage soil microbial activities and influence the solubility, availability, and toxicity of heavy metals to soil microbes respectively, thus, decrease the effect of heavy metals on the biochemical reaction in the soil.…”
Section: Distribution Of Soil Enzymescontrasting
confidence: 94%
“…This result is contrary to the results of Gang et al (2017); Tang et al (2019) who revealed significant inhibition of soil enzymes by increases of heavy metals. Furthermore, high temperature and pH at contaminated locations encourage soil microbial activities and influence the solubility, availability, and toxicity of heavy metals to soil microbes respectively, thus, decrease the effect of heavy metals on the biochemical reaction in the soil.…”
Section: Distribution Of Soil Enzymescontrasting
confidence: 94%
“…It consists of mine deposits of different sizes. This mining was explored during 1970–1990s and has been abandoned from approximately 20 years (Yang et al, 2018). Soils of the region have been seriously polluted by numerous metals due to mining activities.…”
Section: Methodsmentioning
confidence: 99%
“…As a rule, these waste materials still contain huge amounts of long-lived radionuclides, for example, uranium, thorium, radium and others, as well as associated typical heavy metals (for example, Cd, Pb, Cr, etc.) and metalloids (for example, As) [7,[9][10][11]15]. These radionuclides and heavy metals/metalloids may be influenced by natural or human factors and may migrate into environmental media, thus affecting the soil ecosystem, food chain, and human health around tailings ponds [9,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…and metalloids (for example, As) [7,[9][10][11]15]. These radionuclides and heavy metals/metalloids may be influenced by natural or human factors and may migrate into environmental media, thus affecting the soil ecosystem, food chain, and human health around tailings ponds [9,10,15]. Researchers in Portugal, the UK, and China have carried out investigations on the distribution of radionuclides and heavy metals/metalloids in uranium mining areas.…”
Section: Introductionmentioning
confidence: 99%